Race talk Languages of racism and resistance in Neapolitan street markets - Dawes, Antonia Lucia (Manchester University Press, 2020)
Race talk is about language use as an anti-racist practice in multicultural city spaces. The book contends that attention to talk reveals the relations of domination and subordination in heterogeneous, ethnically diverse and multilingual contexts, while also helping us to understand how transcultural solidarity might be expressed.Drawing on original ethnographic research conducted on licensed and unlicensed market stalls in in heterogeneous, ethnically diverse and multilingual contexts, this book examines the centrality of multilingual talk to everyday struggles about difference, positionality and entitlement. In these street markets, Neapolitan street vendors work alongside documented and undocumented migrants from Bangladesh, China, Guinea Conakry, Mali, Nigeria and Senegal as part of an ambivalent, cooperative and unequal quest to survive and prosper.As austerity, anti-immigration politics and urban regeneration projects encroached upon the possibilities of street vending, talk across linguistic, cultural, national and religious boundaries underpinned the collective action of street vendors struggling to keep their markets open. The edginess of their multilingual organisation offered useful insights into the kinds of imaginaries that will be needed to overcome the politics of borders, nationalism and radical incommunicability.